An Analysis of Writing Descriptive Text at the Second Semester Students’ English Language Teaching UNU Purwokerto - Haris Mayekti, Meilina; Faiza, Dinar; Christanty Yudha Bestari, Ade (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2022)
This was a descriptive research project. The goal of this study was to find out how well students could write descriptive texts. The goal is to evaluate the pupils' abilities to write descriptive material. The study looked at five aspects of the students' writing. They're working on formulating ideas, organizing them, using syntax, vocabulary, and mechanics. In addition, there are five categories in which students' writing might be evaluated. Excellent, good, satisfactory, weak, and poor are the four options. The findings of this study concern text composition, the difficulty of performing well-organized writing, the processing of writing order, and language selection. They write the words that aren't appropriate. They use words that are inappropriate for the circumstance. It's all about the grammar here. The kids were grammatically correct. That is the present tense in its simplest form. The students can also put mechanics together well. In their writing, they are things like punctuation, spelling, and capitalization. It occurred as a result of the students' own lack of effort. The kids are aware of the rules of writing, but they are unable to apply them. As a result, the students' writing skills are still lacking.